Fatigue implications for bending orthopaedic plates. Issue 10 (October 2021) - Parr, William C.H.; Wang, Tian; Tan, Christopher; Dan, Michael J.; Walsh, William R.; Morberg, Per
Highlights: When using orthopaedic plates to stabilise fractures, surgeons are faced with the choice of whether to bend the plate to fit better the patient's anatomy, or whether to use the plate as designed. Does pre-bending orthopaedic plates negatively impact their fatigue strength? In vitro 4-point bending static and fatigue testing according to the ASTM F382 standard, with In silico linear and non-linear Finite Element Analysis (FEA) replicating the mechanical test set up Pre-bending of the orthopaedic plates tested here increased the fatigue strength of plates This occurs through work hardening the bent region, as confirmed by the non-linear FEA modelling. Abstract: Objectives: - We aimed to investigate how pre-bending affects the mechanical properties, specifically fatigue, of stainless-steel plates. Methods: - 3.5mm LCP 10-hole plates were pre-bent in 1, 2 and 3 locations to the same overall degree and fatigue testing performed. Finite Element Analysis (FEA) was performed in Strand7 (version 2.4.6) to better understand the failure point of the plates in four-point bending. Results: - Six different plate pre-bending conditions were tested for resistance to fatigue failure. Increasing the number of pre-bends improved the fatigue resistance with two pre-bends having a mean 509, 304 cycles to failure and three pre-bends 491, 378 cycles to failure. The region of highest stress and the point of fatigue failure were at the plate's minimum cross-sectional area, which was predicted by the FEA and confirmed with mechanical testing. For plates pre-bent in two locations, the fatigue failure always occurred in the screw hole not in between the positions of the two pre-bends. Non-linear FEA simulation confirmed that work hardening occurs around pre-bend locations, conferring increased fatigue resistance to the holes next to, or between, pre-bend locations. Conclusions: We found that contrary to orthopaedic folklore, pre-bending of plates is not detrimental to fatigue resistance of the stainless-steel plates we tested. Pre-bending plates in a single plane increased the fatigue properties of the 10-hole stainless-steel plate tested.